The relationship between credit ratings and asset liquidity : Evidence from Western European banks - Meriläinen, Jari-Mikko; Junttila, Juha (Elsevier, 2020)
This study examines the role of asset liquidity in Western European banks’ credit rating downgrades and upgrades over the 2005–2017 period. The results suggest that changes in bank credit ratings have been more favorable for banks that have a liquid asset portfolio. Furthermore, asset liquidity has a stronger effect on the credit rating of banks that already have an illiquid asset portfolio. In contrast, the effect is significantly smaller or nonexistent for the most liquid banks. These results imply that the new liquidity regulation introduced by the Basel III requirements will improve the stability and hence decrease the fragility of the European banking sector. Furthermore, the benefits are highest for the most illiquid banks. In addition, the sovereign credit rating pass-through effect is strongest for illiquid banks.
Keywords: Sovereign effect; liquidity; banks (monetary institutions); credit ratings; fi=Taloustiede|en=Economics|